Big Data – The New Oil Of 21st Century And Hadoop (Trinity Journal of Management, IT & Media (TJMITM), 2016)
BIG DATA Big data is a collection of data sets so large and complex that it  becomes difficult to process using on -hand database management  tools.Big data can be called as data that’s an order of magni tude greater than data you’re accustomed to.They constitute both  structured and unstructured data that grow large so fast that they  are not manageable by traditional relational database systems or  conventional systems. HADOOP Hadoop was created by DOUNG CUTTING and MICHAEL CA FARELLA in 2005,both worked for Yahoo.Doung had an elephant  whose name was HADOOP. Hadoop is an open-source software  framework for storing and processing big data in a distributed  fashion on large clusters of commodity hardware. Essentially, it  accomplishes two tasks: massive data storage and faster process ing.
Keywords: Big Data; Hadoop; Large Data Set; Complex Data Set; Open Source Software